Chicken Little - Dindal, Mark.; Fullmer, Randy; Bencich, Steve; Walt Disney Pictures (United States Walt Disney Pictures ; distributed in the Philippines by Viva Video, 2006)
After ruining his reputation with the town, a courageous chicken must come to the rescue of his fellow citizens when aliens start an invasion.
Editor, Dan Molina ; music, John Debney ; production designer, David Womersley ; design, Mac George ; art director, Ian Gooding ; visual effects supervisor, Steve Goldberg.
Voices: Zach Braff, Garry Marshall, Don Knotts, Patrick Stewart, Amy Sedaris, Steve Zahn, Joan Cusack, Wallace Shawn, Harry Shearer, Fred Willard, Catherine O'Hara, Adam West.
VCD.
Keywords: Children's films; Comedy films